Unconventional Resources in India: The Way Ahead - Sharma, Shivanjali; Saxena, Amit.; Saxena, Neha.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book addresses unconventional hydrocarbon resources in India and the prospects for their exploitation. Each chapter focuses on a particular unconventional resource, including gas hydrates, coal bed methane and shale, while the book as a whole takes into account the government$1 (Bs projections concerning these resources. The book provides readers with essential information on the nation$1 (Bs energy requirements, methods of exploiting its available unconventional resources, and their contribution to meeting India$1 (Bs energy requirements. It also addresses the various geological conditions that are necessary for the exploration of these resources, and enables readers to understand the challenges that need to be overcome. Its logical, clearly structured chapters make the book an ideal starting point for readers interested in unconventional energy resources. It will especially benefit undergraduate and graduate students in the field of Energy Engineering, as well as academic researchers and industry professionals seeking an overview of the status quo of unconventional hydrocarbon resources in India.s
Part One: Introduction to Gas Hydrates -- Hydrates and their Properties -- Gas Hydrate Formation -- Application of Gas Hydrates -- Challenges in Gas Hydrate Formation in Oil Industry -- Conclusions -- Part Two: Introduction to Coal Bed Methane (CBM) -- Geology of Probable Areas and Its Petrology -- Gas content Measurement in Coalbed: Desorption Test and Isotherm Study -- Recovery of methane and CO2 sequestration -- Conclusions -- Part Three: Introduction to Shale -- Global Scenario -- Shale Resources in India -- Major Challenges in Shale Exploration -- Conclusions.
Keywords: Natural resources; Fossil fuels; Energy policy; Energy and state; Natural Resource and Energy Economics; Fossil Fuels (incl. Carbon Capture).; Energy Policy, Economics and Management